Penentuan Setting Optimal Dengan Menggunakan Metode Taguchi Dalam Proses Produksi Gypsum Interior Berdasarkan Pengujian Kuat Desak - Dani, Instika; Herdiman, Lobes; Pujiyanto, Eko (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2005)
The Taguchi Method is one of method that is applied in off line control activities in the design ofproduction process stage. In the production process of interior gypsum, there are many handicaps found when gypsum is going to be taken out of the matrix and placed. Thus, it will make loss in both the company and the customers. The goal of this research is to determine influential factors to the produced interior gypsum, to determine Analysis of variance (Anova) and to count Signal to Noise Ratio (SN ratio), to determine the best setting level from the influential factors, and to count the quality loss function for knowing the loss made by handicapped product. This research uses experiment method and the experiment is done in three stages. The first is based on the company setting and uses 30 samples. The second is based on the applied orthogonal array, L8 (27), and uses 4 replications for every level combination. The third is based on optimum setting and uses 10 samples. From the data processing, there is average rise of compressive strength examination up to 12,63 kg/cm2. This optimum setting will reduce the loss experienced by the company and customers. It can be seen from the value of quality loss function gained before and after applying optimum setting.